Influence of growth regulator Match and Biological insecticide Agerin on the biology of pupae and Adult of cotton leaf worm Spodoptera littoralis (Boisd) (Lepidoptera : Phalaenidae) - AI- Zubadi, A. N. Oueed; AI-Ruba, A R L.; Al-Bakri, A. A. Abas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This experiment was carried out to evaluate the efficiency Â·of growth regulator (Match) and biotic pesticides (Agerin) on the pupa and adult stages of cotton leaf worm Spodoptera littoral is Boisd) that developed from the 1 51 larval instar fed on food treated with different concentration of these pesticides for different’ periods. Result showed that their was a significant decreases in pupal period pupal weight, pupal length, abnonnal growth for pupal stage . A significant decrease in the emergence percentage of adults from these pupa , adult longevity Â·adult age , hatchability gf eggs , male : female. ratio and abnormal growth. for adult stage was also noted . The laboratory studies showed that the lOR ’s Match was more effective than Agerin in all concentrations and periods of feeding .The three days feeding periods als.o were more effective than the- one day feeding period in this regard.